Method for preparing thick perovskite film and radiation detector comprising thick perovskite film
The preparation of a thick perovskite film with nanosheet structure through ultrasonic spraying method solves the problem of insufficient thickness and stability of the traditional perovskite film, and achieves efficient X-ray absorption and heat resistance and moisture resistance.
Patent Information
- Application Number
- CN202311598163.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-17
- Filing Date
- 2023-11-28
- Publication Date
- 2025-04-18
AI Technical Summary
Traditional perovskite films have shortcomings in thickness and stability, making them difficult to effectively absorb X-rays, and are not resistant to heat and humidity in atmospheric environments.
The perovskite thick film was prepared by ultrasonic spraying method, and the perovskite thick film with nanosheet structure was formed by repeated spraying and annealing treatment, combining surfactant and ligand to improve the uniformity and stability of the film.
It realizes high uniformity and stability of perovskite thick film, can effectively absorb and block X-rays, has heat and humidity resistance, and can perform uniform detection on a large area.
Smart Images

Figure CN119855261A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a perovskite thick film, a preparation method thereof, and a radiation detector comprising the perovskite thick film. The radiation detector proposed in the present disclosure is heat-resistant, moisture-resistant, has a controllable radioluminescence wavelength and a low half-maximum full width, and can perform large-area and uniform detection. Background Art
[0002] Radiation detectors (such as X-ray detectors) have many important applications in medical imaging, security monitoring, material analysis, etc. In previous studies, it has been found that perovskite materials have a large radiation absorption coefficient and a high carrier mobility-lifetime product (about 10 -2 cm 2 V -1 ) and other unique advantages, and is considered to be one of the new radiation detector materials. It has the characteristics of high sensitivity and can obtain data with low doses of radiation, thereby reducing the exposure dose.
[0003] Due to the extremely strong penetrability of X-rays, perovskites need to have sufficient thickness to fully absorb X-rays. However, when perovskite films are prepared by traditional methods such as spin coating and doctor blade coating, the thickness is usually not sufficient, making it difficult to achieve effective absorption of X-rays.
[0004] In addition, most of the current research on using perovskites as radiation detector materials often uses quantum dot structured perovskite scintillators. However, this type of perovskite scintillator is not heat-resistant and moisture-resistant in the atmospheric environment, and its stability is not ideal. If the amount of ligand is increased to improve stability, it will adversely lead to a decrease in the intensity of radioluminescence.
[0005] On the other hand, the demand for large-area testing is also increasing, but when the area is increased, the first problem to be faced is uniformity. Summary of the invention
[0006] In view of this, the present disclosure provides a radiation detector, characterized in that it includes: a substrate; a pixel array formed on the substrate; a perovskite thick film with a nanosheet structure formed on the pixel array; and a reading circuit electrically connected to the pixel array, wherein the perovskite thick film includes CsPbBr m I 3-m or FAPbBr m I 3-m , and 0≤m≤3, wherein the perovskite thick film includes a surfactant and a ligand.
[0007] The present disclosure also provides a method for preparing a perovskite thick film, characterized in that it includes: a) providing a perovskite precursor solution; b) spraying the perovskite precursor solution on a substrate to form a perovskite film; c) repeating step b) to form a perovskite thick film; and d) annealing the perovskite thick film to obtain a perovskite thick film with a nanosheet structure.
[0008] The perovskite thick film prepared in the present disclosure has a nanosheet structure and can reach a thickness of more than 60 μm through repeated spraying, which can effectively block and absorb radiation. The surface of the perovskite prepared in the present disclosure is also very flat and uniform, so it can be used to prepare a high-sensitivity, high-resolution radiation detector. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figures 1A to 1D The scanning electron microscope (SEM) photos of the perovskite precursor solution of Example 1 without ultrasonic oscillation pretreatment and after ultrasonic oscillation pretreatment for 1, 5, and 10 minutes, respectively;
[0010] Figures 2A to 2D They are respectively the SEM top view, SEM cross-sectional view, SEM cross-sectional view and transmission electron microscope (TEM) photograph of the ultrasonic spraying perovskite thick film of Example 2;
[0011] Figures 3A to 3C They are respectively the SEM top view, SEM cross-sectional view and TEM photograph of the drop-cast perovskite film of Example 2;
[0012] Figure 4 X-ray diffraction (XRD) diagram of each perovskite film in Example 3;
[0013] Figure 5 is a radioluminescence (RL) intensity diagram of each perovskite film in Example 4;
[0014] Figure 6 The relationship diagrams of thickness-photoluminescence quantum yield (PLQY) and thickness-RL intensity of each perovskite film in Example 4;
[0015] Figure 7 RL diagram of large-size ultrasonic spraying perovskite thick film in Example 4;
[0016] Fig. 8A and 8BThe modulation transfer function (MTF) of the drop casting perovskite film and the ultrasonic spraying perovskite thick film of Example 4 are calculated by back-calculation through CCD camera imaging;
[0017] Fig. 9 The optical microscope photo and interface analysis of the ultrasonic spraying perovskite thick film of Example 5;
[0018] Fig.10 The photoluminescence (PL) wavelength and full width at half maximum distribution diagram of the ultrasonic spraying perovskite thick film and commercially available quantum dot (QD) material in Example 5;
[0019] Fig.11 The PL wavelength and half-maximum full width distribution diagram of the ultrasonic spraying perovskite thick film of Example 6 including different surfactants;
[0020] Fig. 12A and 12B RL diagrams of nine positions taken for the ultrasonic spraying method perovskite thick film on the hard board and the soft board in Example 7;
[0021] Fig.13 RL diagram of ultrasonic spraying perovskite thick film with different ligands in Example 8;
[0022] Fig.14A and 14B They are TEM photos of perovskite thick films prepared by ultrasonic spraying with different ligands in Example 8;
[0023] Figures 15A to 15C TEM images of the ultrasonic spraying CsPbBr3 thick film of Example 9, the ultrasonic spraying CsPbI3 thick film and the commercially available QD CsPbBr3 thick film;
[0024] Fig.16 RL diagrams of the ultrasonic spraying CsPbBr3 thick film and the commercially available QD CsPbBr3 thick film of Example 9;
[0025] Fig.17 RL diagram of the CsPbI3 thick film produced by ultrasonic spraying in Example 9;
[0026] Fig.18A and 18B RL diagrams taken at 9 positions for the commercially available quantum dot perovskite film and the soft plate ultrasonic spraying method perovskite thick film in Example 10;
[0027] Fig.19 RL diagram of commercially available quantum dot perovskite film, hard board and soft board ultrasonic spraying perovskite thick film in Example 10;
[0028] Fig. 20A This is a photo of an application example of ultrasonic spraying perovskite thick film in the field of medical testing in Example 11; Figures 20B to 20C photos of application examples of industrial destructive testing; and
[0029] Fig.21 This is a schematic diagram of the structure of the radiation detector of Example 11.
[0030] [Description of Reference Numerals] 10 substrate
[0031] 11 Reading Circuit
[0032] 12 Control Circuit
[0033] 20 Perovskite Thick Film
[0034] 30 pixel array
[0035] 31 Photoelectric conversion element
[0036] 40 protective layers. DETAILED DESCRIPTION
[0037] The following describes the implementation of the present disclosure through specific specific examples, and those skilled in the art in the technical field to which the present disclosure belongs can easily understand the scope and efficacy of the present disclosure based on the contents described herein. However, the specific embodiments described herein are not intended to limit the present disclosure, and the various technical features or schemes listed may be combined with each other, and the present disclosure may also be implemented or applied through other different implementations, and the various details described herein may also be given different changes or modifications according to different viewpoints and applications without departing from the present disclosure.
[0038] When “includes,” “comprising,” or “has” specific elements as described herein, unless otherwise stated, other elements, components, structures, regions, parts, devices, systems, steps, or connections may also be included, rather than excluding such other elements.
[0039] Unless clearly stated otherwise herein, the singular forms "a", "an" and "the" described herein also include plural forms, and "or" and "and / or" described herein are used interchangeably.
[0040] The numerical ranges described herein are inclusive and combinable, and any numerical value falling within the numerical range described herein can be used as the maximum value or the minimum value to derive its sub-range; for example, the numerical range of "520nm to 600nm" should be understood to include any sub-range between the minimum value 520nm and the maximum value 600nm, such as: 520nm to 590nm, 530nm to 600nm and 530nm to 590nm and other sub-ranges; in addition, if a numerical value falls within the various ranges described herein (such as 550nm falling between 520nm and 600nm), the numerical value should be deemed to be included in the scope of the present disclosure.
[0041] The present disclosure provides a perovskite thick film and a method for preparing the perovskite thick film. The method for preparing the perovskite thick film comprises:
[0042] a) providing a perovskite precursor solution;
[0043] b) spraying the perovskite precursor solution on a substrate to form a perovskite film;
[0044] c) repeating step b) to form a perovskite thick film; and
[0045] d) performing annealing treatment on the perovskite thick film to obtain a perovskite thick film with a nanosheet structure.
[0046] In some embodiments, the perovskite precursor solution includes a perovskite precursor salt, a surfactant, a solvent, and a ligand.
[0047] In some embodiments, the perovskite precursor salt includes CsPbBr m I 3-m or FAPbBr m I 3-m And 0≤m≤3, for example: CsPbBr3, CsPbBr 1.5 I 1.5 、FAPbBr3、FAPbBr 1.5 I 1.5 .
[0048] In some embodiments, the ligand is a carboxylic acid with a carbon number of eight or more and a primary amine. In some embodiments, the carbon number is eight to twelve, for example: octanoic acid, nonanoic acid, decanoic acid, undecanoic acid and dodecanoic acid; octylamine, nonylamine, decylamine, undecylamine and dodecylamine. In other embodiments, the ligand is octanoic acid and octylamine, or decanoic acid and decylamine.
[0049] In some embodiments, the surfactant is a nonionic surfactant. In other embodiments, the surfactant is at least one selected from the group consisting of Tween 20, Tween 40, Tween 60, Tween 65 and Tween 80.
[0050] The surfactant helps the perovskite precursor solution to self-assemble when the droplets are sprayed on the substrate surface, effectively reducing the surface tension caused by capillary phenomena, allowing the perovskite thick film to have a nanosheet structure and high uniformity.
[0051] In some embodiments, the surfactant is present in the perovskite precursor solution in an amount of 0.001 to 0.2 wt %, or 0.005 to 0.05 wt %, for example 0.005, 0.01, 0.02, 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, 0.045, 0.05, 0.06, 0.07, 0.08, 0.1, 0.2 wt %.
[0052] In yet other embodiments, the surfactant is 0.005 to 0.05 wt % Tween 60.
[0053] In some embodiments, the solvent may be at least one of the group consisting of toluene, dimethyl sulfoxide (DMSO), N-dimethylformamide (DMF), γ-butyrolactone (GBL), N,N-dimethylacetamide (DMAC), ethanol, isopropanol, n-propanol, n-butanol, isobutanol, and n-hexane.
[0054] In some embodiments, in the perovskite precursor solution, the surfactant:ligand:solvent is 0.8-1.2:0.8-1.2:1.
[0055] In some embodiments, the spraying in step b) is ultrasonic spraying. In other embodiments, the ultrasonic power is 1W to 3W, such as 1, 1.5, 2, 2.5, 3W; the discharge speed is 0.1mL / min to 3mL / min, such as 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.5, 2, 2.5, 3mL / min.
[0056] In some embodiments, the nozzle will move from the initial position during the spraying of step b) to spray the perovskite precursor solution at various positions on the surface of the substrate, and then the nozzle will return to the initial position and spray the perovskite precursor solution on the substrate again to achieve repeated spraying of step c), thereby preparing a perovskite thick film. In other embodiments, the nozzle movement speed is 1 mm / s to 50 mm / s, for example 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50 mm / s.
[0057] In some embodiments, the film formation after the perovskite precursor solution is sprayed on the substrate is carried out at room temperature (20°C to 25°C). In other embodiments, when the perovskite precursor solution is sprayed on the substrate, the substrate is heated, that is, the method of the present disclosure may further include step e): heating the perovskite film or the perovskite thick film. In some other embodiments, the heating temperature is 25 to 200°C, for example: 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160, 165, 170, 175, 180, 185, 190, 195, 200°C. In other embodiments, the heating temperature is, for example, 30 to 200°C, 40 to 180°C, 50 to 160°C, or 60 to 140°C.
[0058] In some embodiments, the method of the present disclosure may further include step f): pre-treatment of the perovskite precursor solution by shaking, which is between step a) and step b). In other embodiments, the pre-treatment by shaking is ultrasonic shaking, and the ultrasonic shaking power may be 100W to 200W, for example, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200W. In other embodiments, the ultrasonic shaking power may be, for example: 110W to 190W, 120W to 180W, 130W to 170W, 140W to 160W. The pre-treatment time is 1 to 10 minutes, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 minutes. In some other embodiments, after implementing step f) to pre-treat the perovskite precursor solution by shaking, step b) is implemented within one hour.
[0059] The perovskite thick film of the present disclosure can be prepared according to the above method of the present disclosure, but the perovskite thick film of the present disclosure can also be prepared by other methods not limited to the above method.
[0060] The present disclosure provides a perovskite thick film having a nanosheet structure and comprising perovskite, a surfactant and a ligand.
[0061] In some embodiments, the surfactant is a nonionic surfactant. In other embodiments, the surfactant is polysorbate (Tween), poloxamer, fatty alcohol, Triton, octylphenol ethoxylate (IGEPAL), which is at least one selected from the group consisting of Tween 20, Tween 40, Tween 60, Tween 65, and Tween 80. In some further embodiments, the surfactant is Tween 60.
[0062] In some embodiments, the perovskite thick film has an X-ray diffraction analysis (XRD) pattern having a (100) signal of 3.9±0.3°, a (200) signal of 7.6±0.3°, and a (220) signal of 11.4±0.3°.
[0063] In some embodiments, the perovskite thick film has a thickness of 60 to 1000 μm, such as 60 to 1000 μm, 80 to 900 μm, 90 to 800 μm, 100 to 700 μm, or 200 to 600 μm.
[0064] The present disclosure further provides a radiation detector, comprising a substrate, a pixel array formed on the substrate, a perovskite thick film formed on the pixel array and having a nanosheet structure, and a reading circuit electrically connected to the pixel array, wherein the perovskite thick film is as described in the present disclosure and will not be described in detail below.
[0065] In some embodiments, the perovskite thick film has a detection surface with an area of 200 to 2500 cm 2 , for example 200, 400, 600, 800, 1000, 1200, 1400, 1600, 1800, 2000, 2200, 2400 or 2500 cm 2 .
[0066] In some embodiments, the radiation detector is an indirect radiation detector. When the radiation irradiates the perovskite thick film, the X-rays will be converted into visible light, and the TFT array can collect the visible light, so the radiation amount can be obtained by processing and analyzing the visible light. The radiation detector further includes a photoelectric conversion element, such as a switching diode, which can convert the visible light into an electrical signal. The electrical signal is read out by a multiplexer under the control of the control circuit, and the read signal is handed over to the back-end software for processing and imaging.
[0067] In some embodiments, the radiation detector is an X-ray sensor, a gamma ray sensor, or an X-ray and gamma ray sensor.
[0068] In some embodiments, the pixel array includes a charge coupled device (CCD), a complementary metal oxide semiconductor (CMOS), a thin film transistor (TFT), an indium gallium zinc oxide (IGZO), or a photomultiplier tube (PMT).
[0069] In some embodiments, the material forming the substrate is selected from the group consisting of glass, polyethylene terephthalate (PET), polydimethylsiloxane (PDMS), aluminum, rubber (e.g., ethylene propylene diene methylene rubber, styrene butadiene rubber, silicone rubber), fluorine-containing polymers (e.g., polytetrafluoroethylene, perfluoroalkoxyalkane, ethylene tetrafluoroethylene), optical fiber board, silicon dioxide (SiO2), ceramics (e.g., silicon nitrate, silicon carbide, aluminum oxide, and boron carbide). In other embodiments, the material forming the substrate is selected from the group consisting of PDMS, SiO2, PET, and glass.
[0070] In some embodiments, the wavelength of the radioluminescence (RL) of the radiation detector is between 520nm and 600nm, for example, 520, 525, 530, 535, 540, 545, 550, 555, 557, 560, 565, 570, 575, 580, 585, 590, 595, 600nm; the half-maximum full width of the RL of the radiation detector is less than 25nm, for example, 25, 24, 23, 22, 21, 20nm.
[0071] The present disclosure will be described in further detail with reference to the following examples, which are however in no way intended to limit the scope of the present disclosure.
[0072] Example 1 - Pre-Oscillation Processing Diagram
[0073] First, a 3.2mM perovskite precursor solution was prepared, with 0.3071g of cesium acetate (CsAc, 1.6mmole) and 1.1477g of lead bromide (PbBr2, 3.2mmole) as perovskite precursor salts, 0.02wt% Tween 60 as a surfactant, octanoic acid and octylamine as ligands, and toluene as a solvent, wherein the volume ratio of toluene: octanoic acid: octylamine was 1:1:1. Then, the perovskite precursor solution was subjected to ultrasonic oscillation at a power of 150W for 1, 5, and 10 minutes. The SEM images of the perovskite precursor solution subjected to ultrasonic oscillation are shown as follows: Figure 1B , 1C , 1D, while the SEM image of the perovskite precursor solution without ultrasonic vibration is as follows Figure 1A As shown. Figures 1A to 1D Ultrasonic vibration pretreatment can improve the aggregation problem of perovskite colloidal particles and enhance dispersibility. On the other hand, due to the improved dispersibility, it can also avoid the precipitation and blockage of perovskite precursor solution that may occur during the process.
[0074] Example 2 - Ultrasonic spraying
[0075] The perovskite precursor solution was prepared as in Example 1, and then the perovskite precursor solution was coated on the substrate by ultrasonic spraying in an atmospheric environment. The substrate was heated by a heating plate below, the heating plate was set to a temperature of 50°C, the ultrasonic nozzle power was 3W, the discharge speed was 0.5mL / min, and the nozzle movement rate was 15mm / s. After spraying one layer, the spraying was repeated to obtain a perovskite thick film with a thickness of 93.5μm. The SEM image is as follows: Figure 2A As shown, SEM cross-sectional photographs are shown Figure 2B and 2C As shown, TEM photos are Figure 2D shown.
[0076] For comparison, a perovskite precursor solution was prepared in the same manner as above, but was coated on a substrate by drop casting to obtain a perovskite film. The SEM image of the film is shown in FIG. Figure 3A As shown, the SEM cross-sectional photograph is Figure 3B As shown in the TEM photos Figure 3C shown.
[0077] according to Figures 2A to 2D Ultrasonic spraying of perovskite thick films and Figures 3A to 3C The drop-casting method of perovskite film and perovskite thick film disclosed herein adopts ultrasonic spraying, which can effectively improve the problem of micron-level pinholes in the film, and can also produce vertically oriented and micron-level thick films.
[0078] Example 3 - X-ray diffraction (XRD) analysis
[0079] The drop casting method perovskite film and the ultrasonic spraying method perovskite thick film were prepared in the same manner as in Example 2. Among them, the ultrasonic spraying was repeated 5 times, 10 times and 15 times to prepare three ultrasonic spraying method perovskite thick films respectively. The XRD of each film layer is as follows Figure 4 As shown in the figure, it can be seen that the XRD of the ultrasonic spraying perovskite thick film has (100), (200), and (300) signals, which shows that the perovskite thick film produced by ultrasonic spraying has a highly ordered superstructure. However, the XRD of the drop casting perovskite film does not have these signals or they are very weak, that is, the molecular arrangement order is relatively low.
[0080] Example 4 - Radioluminescence (RL) wavelength, intensity and photoluminescence quantum yield (PLQY)
[0081] A drop-cast perovskite film with a thickness of 38 μm and an ultrasonic sprayed perovskite thick film with thicknesses of 35 μm, 66 μm and 93 μm (controlled by the number of repetitions of ultrasonic spraying) were prepared in the same manner as in Example 2. X-rays (model MyVet X500 X-ray: 80 kVp, 5 mA, purchased from Woorien, the same below) were irradiated to each film layer, and the RL intensity and PLQY generated by each film layer were recorded, as shown in FIG. Figure 5 and Figure 6 As shown. It can be seen that the PLQY of the ultrasonic spraying perovskite thick film decreases slightly with thickness, but is still greater than the PLQY of the drop casting perovskite film. In addition, although the PLQY of the ultrasonic spraying perovskite thick film decreases slightly with thickness, this is caused by the self-absorption of the perovskite thick film. On the other hand, the RL strength of the ultrasonic spraying perovskite thick film is also greater than the RL strength of the drop casting perovskite film. In addition, the RL strength of the ultrasonic spraying perovskite thick film increases with thickness, which is caused by the increase in the ability of the perovskite thick film to block high-energy electrons.
[0082] A large-sized ultrasonic spraying perovskite thick film was prepared using the method of Example 2, wherein the heating temperature of the heating plate below the spraying substrate was adjusted to 30°C and the film area was 15×15 cm 2 . X-rays are irradiated on the ultrasonic sprayed perovskite thick film, and the RL intensity generated is recorded, such as Figure 7 As shown. Figure 7 The half-maximum full width of the ultrasonic spraying perovskite thick film can reach 21nm, which is significantly better than the half-maximum full width of the known drop casting perovskite film, such as that shown in Nano Res. 2022, 15(3), 2399-2404.
[0083] Furthermore, the preparation method of Example 2 was used to prepare a drop casting perovskite film and an ultrasonic spraying perovskite thick film, but the heating temperature of the heating plate under the spraying substrate was adjusted to 30°C, and the RL generated by the film layer after X-ray irradiation was imaged by a CCD camera, and the modulation transfer function (MTF) was calculated back to be 0.20 (@2lp / mm) and 0.29 (@2lp / mm), respectively. Fig. 8A and 8B As shown. The MTF curve shows both resolution and contrast information, and can evaluate the resolution level according to the needs of a specific application. According to this result, when at 2lp / mm, the MTF of the drop-cast perovskite film only reaches 0.20, while the ultrasonic spraying nanosheet perovskite thick film can reach 0.29. Compared with the drop-casting perovskite film, the ultrasonic spraying nanosheet perovskite thick film has a higher resolution.
[0084] Example 5 - Surfactants
[0085] As in Example 2, a perovskite precursor solution without Tween 60 (for comparison) or with 0.02 wt% Tween 60 was used to prepare a perovskite thick film by ultrasonic spraying, but the heating temperature of the heating plate under the spraying substrate was adjusted to 30°C. The optical microscope photos and surface analysis of the above-mentioned film layers are shown in Figure 2. Fig. 9 According to these results, the addition of 0.02 wt% Tween 60 as a surfactant in the perovskite precursor solution can reduce the surface tension, thereby increasing the uniformity of the film.
[0086] Furthermore, each film layer produces fluorescence after 532nm laser irradiation, and the PL wavelength and half-maximum full width are as follows: Fig.10 shown, and Fig.10 The results of commercially available quantum dot perovskite thick film (purchased from Polymer International) were also added for comparison. The results showed that the ultrasonic spraying method can achieve a half-peak full width of about 12 to 14nm, and the addition of Tween 60 as a surfactant during the preparation process can make the half-peak full width at each position of the film more uniform, which is better than the half-peak full width of commercially available quantum dot perovskite thick film (19nm).
[0087] Example 6 - Surfactants
[0088] The preparation method of Example 2 is as follows, and the perovskite precursor solution is prepared by ultrasonic spraying perovskite thick film, wherein the heating temperature of the heating plate under the spraying substrate is adjusted to 30° C. The PL wavelength and half maximum width of each PL generated by fluorescence irradiation are as follows: Fig.11 According to these results, the addition of nonionic surfactants such as 0.01wt% Tween 60, 0.02wt% Tween 60, and 0.08wt% Tween 20 can increase the half-maximum width and PL wavelength uniformity of the film.
[0089] Example 7 - Large-scale ultrasonic spraying of perovskite thick films
[0090] A large-sized ultrasonic spraying perovskite thick film was prepared as in Example 2, wherein the heating temperature of the hot plate below the spraying substrate was adjusted to 30°C, the substrates were selected from hard plates (such as glass) and PET soft plates, and the film area was 15×15 cm 2X-rays were used to irradiate the ultrasonic sprayed perovskite thick films on hard and soft boards, and the RL generated at 9 evenly distributed points on the films was recorded, such as Fig. 12A and 12B As shown. Fig. 12A , the RL wavelength of the perovskite thick film by ultrasonic spraying on hard board is 520±0.16%nm and the RL intensity is 531±0.39%; according to Fig. 12B , the RL wavelength of the perovskite thick film deposited by ultrasonic spraying on the soft board is 520±0.43%nm and the RL intensity is 498±1.31%. These results show that the variation of the RL wavelength and RL intensity of the perovskite thick film deposited by ultrasonic spraying is very low, less than 1.5%, showing very excellent uniformity.
[0091] Example 8 - Ligand
[0092] The perovskite precursor solution was prepared in the same manner as in Example 2, but the ligands were changed to butyric acid and n-butylamine, hexanoic acid and hexylamine, octanoic acid and octylamine, or decanoic acid and decylamine, and the ultrasonic spraying method was used to prepare the perovskite thick film, wherein the heating temperature of the spraying substrate was adjusted to 30°C. The structure was observed, and each was irradiated with X-rays to observe whether it could be successfully detected. The results are shown in Table 1. Fig.13 , Fig.14A and Fig. 14B shown.
[0093] Table 1
[0094]
[0095] According to Table 1, adding octanoic acid and octylamine or decanoic acid and decylamine as ligands can obtain a perovskite thick film with a nanosheet structure, such as Fig.14A and 14B As shown in the TEM photo; and it can produce RL when irradiated with X-rays, such as Fig.13 shown.
[0096] Example 9 - Different Perovskites
[0097] A 3.2 mM perovskite precursor solution was prepared as in Example 2, wherein the perovskite precursor salt was adjusted to 0.3071 g CsAc and 1.4752 g PbI2, and ultrasonic spraying was used to prepare 60 μm thick CsPbBr3 and CsPbI3 perovskite thick films, respectively, wherein the heating temperature of the heating plate under the spraying substrate was adjusted to 30°C. The TEM images of the two are shown as follows: Fig.15A and Fig. 15B A commercially available QD CsPbBr3 perovskite thick film (Quantum Solutions (QS)) was prepared, and its TEM photo is shown in Fig. 15CNext, X-rays were irradiated on each of the above-mentioned film layers and the RL generated was recorded. The RL intensity of the ultrasonic sprayed CsPbBr3 perovskite thick film and the commercially available QD CsPbBr3 perovskite thick film is shown in Fig.16 As shown in Figure 2, the RL strength of the CsPbI3 perovskite thick film produced by ultrasonic spraying is shown in Figure 2. Fig.17 shown.
[0098] These results show that the ultrasonic spraying method can effectively block and absorb X-rays at a thickness of 60μm, and then emit visible light; in contrast, the quantum dot perovskite thick film cannot detect X-rays due to its insufficient thickness.
[0099] Example 10 - Comparison with commercially available QD perovskite films
[0100] Prepare a large-size hard or soft board ultrasonic spraying perovskite thick film in the same manner as in Example 7, with a film area of 15×15 cm 2 The RL generated by X-ray irradiation at 9 evenly distributed points on the soft film is as follows Fig.18B As shown in Figure 2, the RL wavelength is 520±0.16%nm and the RL intensity is 531±0.39%. However, the commercially available quantum dot perovskite film product from Quantum Solutions (QS) (film area is also 15×15 cm 2 ), and 9 evenly distributed positions on the film were taken and irradiated with X-rays. The RL generated was as follows Fig.18A As shown, the RL wavelength is 508±1.69%nm, and the RL intensity is 516±10.1%. The results show that the ultrasonic spraying technology is used to make large-size sensing membranes, and the intensity change is 0.39%, which is better than the 10.1% of QS products; the wavelength change is 0.16%, which is better than the 1.69% of QS products.
[0101] Fig.19 The RL overlays of the ultrasonic spraying perovskite thick film on hard and soft boards and the quantum dot perovskite film from Quantum Solutions are shown in Figure 1. The full width at half maximum of the ultrasonic spraying perovskite thick film on hard or soft boards is 21nm, which is significantly better than the 112nm full width at half maximum of the quantum dot perovskite film from Quantum Solutions.
[0102] Example 11 - Application of X-ray Detector
[0103] The ultrasonic spraying method of the perovskite thick film disclosed in the present invention has high sensitivity and resolution, and can be used as a component of an X-ray detector and in medical detection (such as Fig. 20A As shown, X-ray irradiation of the left hand prosthesis, 80kVp / 160mA / 800ms), industrial destructive testing (such as Fig. 20B and20C As shown, X-rays are used to irradiate the automotive display circuit board, and the line width can be resolved to be about 100μm, 80kVp / 160mA / 800ms) etc.
[0104] The schematic diagram of the X-ray detector structure of this embodiment is shown in FIG. Fig.21 The X-ray detector 1 includes a substrate 10; a pixel array 30 formed on the substrate 10; a perovskite thick film 20 ( Fig.21 The pixel array 30 and the perovskite thick film 20 are shown separately to facilitate the display of the reading circuit 11 and the photoelectric conversion element 31); and the reading circuit 11 electrically connected to the pixel array 30. This X-ray detector 1 converts X-rays into visible light through the perovskite thick film 20, so the X-ray radiation amount can be obtained by processing and analyzing the visible light. Optionally, a protective layer 40 can be formed on the perovskite thick film 20, which is a protective layer with both protective and light reflecting functions, such as: aluminum film. Incidentally, the X-ray detector 1 may also include a photoelectric conversion element 31, which can be arranged on the pixel array 30 and controlled by a control circuit 12 electrically connected thereto, and can convert the visible light generated by the perovskite thick film into an electrical signal, which can then be processed by the back-end software to form an image.
[0105] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A radiation detector, characterized in that: include: a substrate; a pixel array formed on the substrate; A perovskite thick film having a nanosheet structure, formed on the pixel array; as well as a reading circuit electrically connected to the pixel array, Wherein, the perovskite thick film includes CsPbBr m I 3-m or FAPbBr m I 3-m , and 0≤m≤3, Wherein, the perovskite thick film includes a surfactant and a ligand.
2. The radiation detector according to claim 1, wherein: The surfactant is at least one selected from the group consisting of Tween 20, Tween 40, Tween 60, Tween 65 and Tween 80.
3. The radiation detector according to claim 1, wherein: The surfactant includes 0.005 to 0.05 wt % of Tween 60.
4. The radiation detector according to claim 1, wherein: The ligands are octylamine and octanoic acid, or decanoic acid and decylamine.
5. The radiation detector according to claim 1, wherein: The X-ray diffraction analysis spectrum of the perovskite thick film has a (100) signal of 3.9±0.3°, a (200) signal of 7.6±0.3°, and a (220) signal of 11.4±0.3°.
6. The radiation detector according to claim 1, wherein: The thickness of the perovskite thick film is 60 to 1000 μm.
7. The radiation detector according to claim 1, wherein: The perovskite thick film has a detection surface, the area of which is 200 to 2500 cm 2 .
8. The radiation detector according to claim 1, wherein: The radiation detector is an X-ray sensor, a gamma-ray sensor, or an X-ray and gamma-ray sensor.
9. The radiation detector of claim 1, wherein the wavelength of the radioluminescence is between 520 nm and 600 nm, the full width at half maximum is less than 25 nm, and the device with a line width of at least 100 μm can be resolved.
10. A method for preparing a perovskite thick film, characterized in that: include: a) providing a perovskite precursor solution; b) spraying the perovskite precursor solution on a substrate to form a perovskite film; c) repeating step b) to form a perovskite thick film; as well as d) performing annealing treatment on the perovskite thick film to obtain a perovskite thick film with a nanosheet structure.
11. The method according to claim 10, wherein: The perovskite precursor solution of step a) comprises a perovskite precursor salt, a surfactant, a ligand and a solvent.
12. The method according to claim 10, wherein: The ligands are carboxylic acids with carbon numbers of 8 to 12 and primary amines.
13. The method according to claim 10, wherein: The ligands are octylamine and octanoic acid, or decanoic acid and decylamine.
14. The method according to claim 10, wherein: The weight percentage concentration of the surfactant is 0.001 to 0.2 wt %.
15. The method according to claim 10, wherein: The surfactant is 0.005wt% to 0.05wt% Tween 60.
16. The method according to claim 10, wherein: In the perovskite precursor solution, the volume ratio of the surfactant: the ligand: the solvent is 0.8-1.2:0.8-1.2:
1.
17. The method according to claim 10, wherein: The perovskite thick film includes CsPbBr m I 3-m or FAPbBr m I 3-m , and 0≤m≤3.
18. The method according to claim 10, wherein: The spraying in step b) is ultrasonic spraying, and the ultrasonic power is 1W to 3W, the discharge speed is 0.1mL / min to 3mL / min, and the nozzle movement speed is 1mm / s to 50mm / s.
19. The method according to claim 10, further comprising step e): heating the perovskite film or the perovskite thick film at a heating temperature of 25 to 200°C.
20. The method according to claim 10, further comprising a step f) between step a) and step b): performing a pre-treatment of the perovskite precursor solution by shaking, wherein the shaking power of the pre-treatment is 100-200 W and the shaking time is 1-10 minutes.